Individuality and Continuity in Narrating across Generations - Skultans, Vieda (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2020)
This article explores the commonalities of structure in the life histories of a mother and her daughter. I argue that sharing the same story does not preclude the existence of a strong and distinctive sense of self. Agency and selfhood are intimately connected with interpretation and the pursuit of understanding. In order to illuminate this relationship, I draw upon ideas of musical form and interpretation that suggest how this might come about.